1989
DOI: 10.1210/jcem-68-1-145
|View full text |Cite
|
Sign up to set email alerts
|

Nontoxic Nodular Goiter and Papillary Thyroid Carcinoma Are Not Associated With Peripheral Blood Lymphocyte Sensitization to Thyroid Cells*

Abstract: We tested the claim that uni- and multinodular goiter (UNG and MNG) and papillary carcinoma (PC) of the thyroid are autoimmune thyroid diseases (AITD) similar to Graves' disease (GD) and Hashimoto's thyroiditis (HT). The expression of HLA-DR on cultured thyroid epithelial cells (thyrocytes) from UNG, MNG, and PC after coculture with autologous peripheral blood mononuclear cells (PBMC) was compared with that on GD and HT cells. The thyrocytes also were cultured with interferon-gamma (IFN gamma) alone. A cytotox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…However, after controlling for other factors, the type of tumor was not an independent predictor for DTC recurrence in the present study. Frequent occurrence of focal lymphocytic infiltration in the thyroid gland is documented in papillary thyroid carcinoma patients (18). Matsubayashi et al (19) found that lymphocytic infiltration of the tumor was related to favorable prognosis in 95 Japanese patients, which contradicts the results of Kamma et al (20).…”
Section: Discussionmentioning
confidence: 93%
“…However, after controlling for other factors, the type of tumor was not an independent predictor for DTC recurrence in the present study. Frequent occurrence of focal lymphocytic infiltration in the thyroid gland is documented in papillary thyroid carcinoma patients (18). Matsubayashi et al (19) found that lymphocytic infiltration of the tumor was related to favorable prognosis in 95 Japanese patients, which contradicts the results of Kamma et al (20).…”
Section: Discussionmentioning
confidence: 93%
“…Likely, all of nine patients had chronic lymphocytic thyroiditis, which had been anticipated based on their underlying heterogeneous parenchyma of the thyroid gland. Even though the prognostic effect of lymphocytic thyroiditis accompanying PTC has been controversial [11,20,21], meticulous care is required in the evaluation of focal lesion with underlying lymphocytic thyroiditis [22]. It is difficult to differentiate WVPTC from dominant lymphocytic infiltration on FNA cytology and the background of lymphocytic thyroiditis may give rise to false negative reports [5,6,17].…”
Section: Discussionmentioning
confidence: 99%
“…It has also been found by RIA in supernatants of thyrocytes cocultured with autologous PB-lymphocytes after 5 or 7 days incubation (Otsubo et al, 1988;Aguayo et al, 1989). However, Otsubo et al (1988) found IFN-y in only 4/14 coculture supernatants.…”
Section: Dlscuorlonmentioning
confidence: 98%